Analisis Kemampuan Computational Thinking Siswa dalam Menyelesaikan Masalah Aritmetika Sosial - Husnani, Tami Maulida; Mahfudy, Sofyan; Afifurrahman, Afifurrahman (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2025)
This study aims to analyze students' computational thinking (CT) skills in solving problems in social arithmetic materials and identify the influence of mathematical initial ability (KAM) on the achievement of CT aspects. This study uses a qualitative approach with a case study type of research. The research subjects consisted of 31 students of class VIII A who were selected through the purposive sampling technique. The data was analyzed using three main stages, namely data reduction, data presentation, and conclusion drawn. The results showed that students with high KAM were able to meet all CT indicators, especially in questions with low difficulty. Students with KAM are showing good achievement but still need reinforcement at the abstraction stage to solve problems systematically. Meanwhile, students with low KAM face difficulties in almost all aspects of CT. This research contributes to the approach to mathematics learning to formulate problems, including identifying the initial ability of mathematics and finding solutions in a systematic way.